Rituximab as first line: an advent in pemphigus - Gopinath, V. P. K.; Kolaparambath, Basheer Ahammed; Simi, V. M.; Rishad, C. M. Ali; Farisa, P. M.; Jose, Tresy (International Journal of Research in Dermatology, 2019)
Rituximab is a newly approved biological wonder drug in pemphigus vulgaris -an autoimmune mucocutaneous blistering disease due to antibodies produced against the epidermal adhesion molecules dsg 1 and dsg 2. The conventional therapy included high dose steroids or immunosuppressants that though effective had significant adverse effects that necessitated an alternate path in treatment. We present a case series of five patients in different clinical scenarios diagnosed with pemphigus vulgaris and treated with Rituximab by RA protocol either sole or in combination with other treatment strategies. Our experience with this drug has paved way to immense possibilities and outcomes that are in favour of using Rituximab as first line option. We have encountered prolonged remission in cases that were treated with Rituximab by Rheumatoid arthritis (RA) protocol. The sustained response has helped in reducing the dose of steroids and other immunosuppressants substantially. These facts are reinforced through our observations. But there is need to standardize the dosage of Rituximab in pemphigus.